Pengaruh Empowerment, Self Efficacy dan Budaya Organisasi terhadap Kepuasan Kerja Karyawan - Pratama, Gede Yoga; Agustina, Made Dian Putri; Gede, I Komang (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
In improving job satisfaction, there are factors that influence job satisfaction such as empowerment, self-efficacy, and organizational culture. This study aims to investigate how empowerment, self-efficacy, and organizational culture affect job satisfaction both partially and simultaneously. The research was conducted at the Courtyard by Marriott Bali Nusa Dua Resort. The total population of all employees at the Courtyard by Marriott Bali Nusa Dua Resort is 247 people. The sample was determined using random sampling with a sample size of 71 people calculated using the Slovin formula. Data were collected through documentation, interviews, and questionnaires, and measured using a Likert scale. The analysis technique used was multiple linear regression. The results show that empowerment partially has a positive and significant influence on job satisfaction, self-efficacy partially has a positive and significant influence on job satisfaction, organizational culture partially has a positive and significant influence on job satisfaction, and empowerment, self-efficacy, and organizational culture simultaneously have a positive and significant influence on job satisfaction. Suggestions include improving empowerment programs through training, boosting self-confidence, and maintaining a positive work culture to foster comfort and job satisfaction among employees..